COVID-19 control school-based interventions: characteristics and impact of a national-level educational programme in Italy - Odone, Anna; Bricchi , Lucia; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2022)
Objective: to report on the characteristics and impact of “Igiene Insieme”, a school-based national-level educational programme designed and implemented in Italy to promote hygiene and sanitation in schools, stimulate healthy behaviors in teachers, students and their families, and ultimately fight COVID-19. Methods: the project targeted kindergartens and primary schools and included three components: the design and delivery of innovative health education interventions to i) students and ii) teachers, and iii) the provision of sanitation products in schools. Here we describe the intervention, report on the project penetration and evaluate its impact. First, a survey was conducted on a convenience sample of 1,005 teachers to evaluate the project at the national level, then a retrospective analysis was conducted in the Lombardy region comparing SARS-CoV-2 infection incidence rate in schools participating to the project with regional burden data.Results: Over 8,000 Italian schools joined the project, for a total of 32,000 teachers and 1.1 million students. Survey respondents rated the educational interventions and the provision of sanitation products as excellent (66.6% and 82.5%, respectively) and reported the project to have greatly impacted on students’ health behaviors. In the Lombardy region, 271 primary schools (11%) joined the project and 140 (52%) provided COVID-19 burden data. Over the study period, SARS-CoV-2 infection incidence rate in schools participating in the project was 14% lower as compared to regional-level data (643 per 100,000 vs. 747 per 100,000).Conclusions: We raise awareness on the importance of promoting health education and infectious diseases primary prevention in schools, and to plan, implement and monitor student-centred interventions during and beyond COVID-19 times.